IMPLEMENTASI PERANCANGAN INTEGRASI SWOT BALANCED SCORECARD DALAM PENILAIAN KINERJA BISNIS PAKAN KELINCI PADA RABBIT BROTHERS DI KABUPATEN BANDUNG - D. Iwan Riswandi; Nurul Husnul Hotimah (JURNAL LENTERA BISNIS, 2024)
Rabbit Brothers is one of the rabbit breeders established in 2017 located in West Java, West Bandung Regency. Rabbit Brothers rabbit feed sales in 2023 fluctuated. The tighter the competition, the company needs to determine strategies in business management to determine the company's current performance. The purpose of this study is to describe the strategy based on SWOT analysis, design a Rabbit Brothers rabbit feed strategy map based on SWOT Balanced Scorecard integration, performance measurement and performance assessment of Rabbit Brothers rabbit feed based on SWOT Balanced Scorecard integration, and improve Rabbit Brothers rabbit feed business performance based on SWOT Balanced Scorecard integration. The methods in this research are SWOT Analysis, Balanced Scorecard, Analytical Hierarchy Process Software Expert Choice, and Key Performance Indicator Lead Indicator. Rabbit Brothers rabbit feed strategy and strategy map, one of which is increasing profits, Rabbit Brothers rabbit feed performance is 93.04%, meaning that the company's performance is in a very healthy condition with the category (AAA). The performance of the four performance perspectives that are not optimal is improved on strategic initiatives, one of which is the content creation program.